Effects of salt purity on lipid oxidation, sensory characteristics, and textural properties of fresh, ground pork patties. (January 2016) - Overholt, M.F.; Mancini, S.; Galloway, H.O.; Preziuso, G.; Dilger, A.C.; Boler, D.D.
Abstract: The objective was to evaluate salts of varying purity levels on lipid oxidation, texture, and sensory properties of fresh ground pork patties. Approximately 160 kg of fresh boneless pork trimmings was used to test a salt typical to industry (treatment A), 3 specialty salts (B, C, and D), and a control (no added salt). Salts were analyzed for Na, Cl, Fe, Cu, Mg, Ca, and Mn content. Experimental treatments were replicated 6 times, for a total of 30 independent batches. Analysis was conducted using the MIXED procedure of SAS as a repeated measure in a complete randomized design. After 11 days of refrigerated storage, there were no differences in lipid oxidation among salts A, C, or D ( P ≥ 0.15), but salt B had less ( P ≤ 0.04) lipid oxidation than salts A, C, and D. However, no differences in oxidized flavor or odor ( P ≥ 0.95) were detected. Overall, salts of varying impurities differed in lipid oxidation but sensory panelists were not able to detect differences in oxidized odors or flavors. Highlights: Salts of varying impurity levels have differing effects on lipid oxidation and discoloration. Trained sensory panelists were unable to distinguish differences in oxidized flavor and odor between salt treatments. Impurities in levels found in salts are of minimal importance to oxidized flavor, odor, texture, and color.